2003
DOI: 10.1373/49.9.1510
|View full text |Cite
|
Sign up to set email alerts
|

Potential Usefulness of Inflammatory Markers to Monitor Respiratory Functional Impairment in Sarcoidosis

Abstract: Background: Sarcoidosis is a multiorgan inflammatory granulomatous disorder of unknown origin for which adequate markers to monitor disease severity are lacking. The aim of this study was to evaluate the potential clinical usefulness of serologic markers of inflammation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
95
1
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(114 citation statements)
references
References 31 publications
9
95
1
9
Order By: Relevance
“…As sarcoidosis is an inflammatory disease, it has been expected to observe increased values of hsCRP, ACE (11,12) and SAA compared to controls (13,14) and our results were in agreement with these findings (Table I). Increased concentrations of SAA may be a consequence of either increased production of proinflammatory cytokines that stimulate hepatic production of SAA (11) or activated cells in granulomas that also produce SAA (15).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As sarcoidosis is an inflammatory disease, it has been expected to observe increased values of hsCRP, ACE (11,12) and SAA compared to controls (13,14) and our results were in agreement with these findings (Table I). Increased concentrations of SAA may be a consequence of either increased production of proinflammatory cytokines that stimulate hepatic production of SAA (11) or activated cells in granulomas that also produce SAA (15).…”
Section: Discussionsupporting
confidence: 92%
“…Increased concentrations of SAA may be a consequence of either increased production of proinflammatory cytokines that stimulate hepatic production of SAA (11) or activated cells in granulomas that also produce SAA (15).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to neopterin, it was elevated in progressive rather than in stable disease or patients with Löfgren syndrome (Ziegenhagen et al, 2003). It was shown to be the most reliable activity marker when compared with hsCRP (hs for high sensitivity), SACE and SAA (Rothkrantz-Kos et al, 2003). The same authors reported that only 7 of 31 untreated patients with low sIL2R values, but 8 of 11 with high sIL2R values needed treatment in follow-up observation (meaning that 73 % of patients with high values, but only 23% of patients with low sIL2R had less favorable outcome).…”
Section: Other Immunological Markersmentioning
confidence: 96%
“…Serum amyloid A (SAA) is another acute phase reactant which is related to HDL-cholesterol. Its diagnostic value in sarcoidosis is similar to CRP (Rothkrantz-Kos et al, 2003), but recent data show its potential role in the pathogenesis of sarcoidosis, as it was shown to be deposited in granuloma cells. This molecule is capable of triggering the release of cytokines through an interaction with toll-like receptor 2 (Chen et al, 2010).…”
Section: Acute Phase Reactantsmentioning
confidence: 97%
See 1 more Smart Citation